Analisis Hukum Islam Terhadap Faktor Pernikahan Dini: Studi Kasus di Desa Bulujaran Kidul Probolinggo - Tosen, Muhammad; Nofita Sari, Zeti (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
This research aims to identify and analyze the factors contributing to divorce in early marriages from the perspective of Islamic law, with a case study focused on Bulujaran Kidul Village. The method used in this research is empirical, involving data collection through in-depth interviews with divorced couples, community leaders, and local authorities. The findings reveal that the main factors contributing to divorce in early marriages include emotional immaturity, economic pressure, and a lack of understanding of rights and obligations in marriage according to Islamic law. Additionally, social and cultural factors also play a significant role in increasing the risk of divorce. This research is expected to provide insights for the community and policymakers in addressing the issue of divorce in early marriages, as well as to encourage better education and understanding of Islamic marriage law.